Psychometric Properties of the Scale for Adolescent Physical Deformities - Abdalla, MEIRI, Elwaleed,; SHABNAN B, AL DAWSARI , HAIFA (Journal of Ecohumanism, 2024)
They aimed to educate current students about the psychometric properties of the adolescent physical deformities scale. The study sample consisted of (293) adolescents. To achieve the study’s objectives, the scale of external appearance anxiety was used Park (2007)and an external rejection sensitivity Scale byRoberts et al. (2018). The scale phrases were translated into Arabic to meet the study objectives.The study findings revealed a strong and statistically significant correlation between the sections of appearance anxiety and sensitivity to external appearance scales, which measure physical deformities in adolescents. The correlation coefficients for the fields ranged from 0.481 to 0.746, a function at the level of (** p <.01) and indicating an acceptable degree of correlation. Results from Bartlett's test for statistical significance of the instruments and measures also showed that the external appearance anxiety scale’s affirmative honesty was computed. From 0.73 to 0.39, the appearance anxiety scale’s assertive honesty coefficients varied. The study outcomes provided further evidence that the domain correlation coefficient was both acceptable and statistically significant. The external appearance anxiety scale's affirmative honesty was determined, and the results of Bartlett's test showed that the tool was statistically significant. The values of affirmative honesty coefficients ranged from 0.775 to 0.38, indicating solid associations between all paragraphs. The study also found that the rejection sensitivity scale reached a coefficient of 0.90, and the external appearance anxiety scale and rejection sensitivity had stability coefficients of 0.86 and 0.91, respectively, according to the McDolland equation.Psychometric Characteristics,